Interaction of α9α10 Nicotinic Receptors With Peptides and Proteins From Animal Venoms - Tsetlin, Victor; Haufe, Yves; Safronova, Valentina; Serov, Dmitriy; Shadamarshan, PranavKumar; Son, Lina; Shelukhina, Irina; Kudryavtsev, Denis; Kryukova, Elena; Kasheverov, Igor; Nicke, Annette; Utkin, Yuri (Frontiers in Cellular Neuroscience, 2021)
Unlike most neuronal nicotinic acetylcholine receptor (nAChRs) subunits, α7, α9, and α10 subunits are able to form functional homo- or heteromeric receptors without any β subunits. While α7 subtype is widely distributed in the mammalian brain and several peripheral tissues, α9 and α9α10 nAChRs are mainly found in the cochlea and immune system cells. α-Conotoxins that specifically block the α9α10 receptor showed anti-nociceptive and anti-hyperalgesic effects in animal models. Hence, this subtype is considered a drug target for analgesics. In contrast to the α9α10-selective α-conotoxins, the three-finger toxin α-bungarotoxin inhibits muscle-type and α7 nAChRs in addition to α9α10 nAChRs. However, the selectivity of α-neurotoxins at the α9α10 subtype was less intensively investigated. Here, we compare the potencies of α-conotoxins and α-neurotoxins at human α9α10 nAChR. Selectivities of toxins were compared by two-electrode voltage clamp analysis on nAChRs expressed in Xenopus oocytes. In addition, we analyzed effects of several α9α10-selective α-conotoxins on mouse granulocytes from mice bone marrow to identify possible physiological functions of the α9α10 nAChR in these cells. The α-conotoxin-induced IL-10 release was measured upon LPS-stimulation. We found that α-conotoxins RgIA, PeIA and Vc1.1 enhance the IL-10 expression in granulocytes which might explain the known anti-inflammatory and associated analgesic activities of α9α10-selective α-conotoxins. Furthermore, we show that two long-chain α-neurotoxins from the cobra Naja melanoleuca venom that were earlier shown to bind to muscle-type and α7 nAChRs, also inhibit the α9α10 subtype at nanomolar concentrations with one of them showing a significantly slower dissociation from this receptor than α-bungarotoxin.